Evaluation of quality of sleep in women with stress urinary incontinence before and after surgical correction - Josyandra Paula de Freitas; Mariana Pereira Inácio Silvestri; César Eduardo Fernandes; Emerson de Oliveira (Einstein (São Paulo))
ABSTRACT Objective: To evaluate the quality of sleep in women with urinary incontinence before and after sling surgery. Methods: A prospective study of case series of women with urodynamic diagnosis of stress urinary incontinence. To evaluate the subjective quality of sleep, two specific questionnaires were used and validated for the Portuguese Language: Epworth Sleepiness Scale and Pittsburgh Sleep Quality Index. The questionnaires were applied before and 6 months after surgical repair. Results: When analyzing the Epworth Sleepiness Scale, there was an improvement in sleep quality (p=0.0401). For the Pittsburgh Sleep Quality Index, only for sleep disorder there was improvement in quality of sleep after surgery (p=0.0127). Conclusion: Women with urinary incontinence, submitted to surgery with sling, showed improvement in both quality of sleep and sleep disorder.